Time Course of Age-Linked Changes in Photosynthetic Efficiency of Spirodela polyrhiza Exposed to Cadmium - Peršić, Vesna; Antunović Dunić, Jasenka; Domjan, Lucija; Zellnig, Günther; Cesar, Vera (Frontiers in Plant Science, 2022)
Short-term assessment of adverse effects is essential for populations exposed to a higher risk of environmental pollution. This paper presents the time-course of physiological and morphological changes attributed to cadmium, emphasizing age-linked differences in the susceptibility of photosynthetic apparatus of Spirodela polyrhiza fronds exposed to different cadmium concentrations. A four-frond colony represented by mothers, daughters, and granddaughter plants was exposed to cadmium concentrations for 6, 24, and 72 h to establish its effect on different generations of the great duckweed. The duration of cadmium exposure accounted for the most variation in chlorophyll content as the most influential variable, and after 72 h, frond responsiveness was a function of cadmium concentration. Carotenoid contents behaved slightly differently in fronds of different ages, with the oldest mother frond exhibiting accelerated senescence. Chlorophyll fluorescence measurements showed that cadmium affects different photosynthetic electron transport segments relative to the frond's chloroplast structure level. Photosynthesis of mother fronds exposed to low cadmium, and daughter fronds exposed to high cadmium, was determined by the functionality of primary electron acceptance at the PSII level. Mother plants exposed to higher cadmium concentrations were characterized by closed and inactive reaction centers, dissipated energy outflux, and inhibited photosynthesis. Young fronds exposed to low and high cadmium concentrations were characterized by increased non-reducing reaction centers and thermal phase reduction, with activated dissipative mechanisms at high cadmium concentrations. Cadmium-induced changes in the ultrastructure of the chloroplasts were visible after six h of exposure to the lowest concentrations with gradual degradation of the thylakoid system as fronds aged. Younger fronds responded to cadmium more dynamically through molecular, physiological, and anatomical changes and tolerated a more reduced electron transport chain under given conditions than older fronds.